Peningkatan Spiritualitas Melalui Zikir Berjamaah (Studi Terhadap Jamaah Zikir Kanzus Sholawat Kota Pekalongan, Jawa Tengah) - Ali Muhtarom ('Anil Islam: Jurnal Kebudayaan dan Ilmu Keislaman, 2016)
Human nature does not just want to be successful in material and social standard. In fact, he has desire to find the ultimate meaning of life based on his own perspective. The quest for the meaning of life could not be enough if just be done using external dimension—it could be reached by spiritual dimension. This study is intended to describe spirituality among the members of Majelis Zikir Kanzus Sholawat in Pekalongan City, Central Java, the form of spirituality, its formative factors, and motivation of the members to attend and join the collective praying. By using a qualitative approach and public opinion surveys, this study shows that the forms of spirituality of Majelis Zikir Kanzus Sholawat could be categorized into three point: (1) meaningful life; (2) more active worship, and (3) a more positive social life. These forms are influenced by two factors: (1) practice the teachings of zikir; (2) understanding the teachings of the leader of majelis zikir. This study also found that there are three motivation among the member of member of Majelis Zikir: a desire to reach spiritual enlightenment, a wish to gain barokah, and a longing for the mursyid (guide) in the tariqa.